Improving students' English pronunciation through drilling technique at SDS Pelangi School - Pratiwi, Theodesia Lady; Simorangkir, Angel Rosinta Uli (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to improve students' English pronunciation through drilling techniques in English subjects for 3rd-grade students at SDS Pelangi School. The subjects of this study were nine which is 3rd-grade students. The instruments used are an observation field note and test and an interview. The study method used is Classroom Action Research. Starting from the problems experienced by students in English pronunciation at SDS Pelangi School are still low. Responding to existing problems, the right technique to improve students' English pronunciation is to use drilling techniques. This study was conducted in two cycles, and the result showed there was also a significant increase in students' pronunciation. The average score of students from Cycle II increased by 10.34 from Cycle I. It can be said that the use of the drilling technique can improve student English pronunciation.